2019
DOI: 10.1177/2050640618809842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high‐volume, intermediate‐volume and low‐volume bowel preparation on colonoscopy quality and patient satisfaction: An observational study

Abstract: Background: Although optimal bowel preparation is essential for high-quality screening colonoscopy, documentation of preparation quality, patient satisfaction and adherence is scarce. Aim: The aim of this article is to compare low-volume (LV, 300 ml sodium picosulfate), intermediate-volume (IV, 2 l polyethylene glycol, PEG þ ascorbic acid and sodium ascorbate), and high-volume (HV, 4 l PEG) purgatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…While the former was compared to high-volume PEG at least in terms of e cacy and tolerability (14), the latter has been compared only with other low-volume preparations (20)(21)(22). Moreover, real-life data are con icting: a recent prospective observational study has shown better cleansing results and higher ADR and AADR with 4L PEG compared to lower volume preparations (23).…”
Section: Discussionmentioning
confidence: 99%
“…While the former was compared to high-volume PEG at least in terms of e cacy and tolerability (14), the latter has been compared only with other low-volume preparations (20)(21)(22). Moreover, real-life data are con icting: a recent prospective observational study has shown better cleansing results and higher ADR and AADR with 4L PEG compared to lower volume preparations (23).…”
Section: Discussionmentioning
confidence: 99%
“…Our first example is a study comparing four different bowel purgatives (A, B, C, and D) and their effect on the quality of colonoscopy. The procedure was called a ‘success’ if the cecum was intubated by the endoscopist, or ‘failure’ otherwise (see [22] for more details). The data set used in a preliminary analysis consisted of 4132 patients and suffered from a separation issue as the cecum of patients that used purgative B, which was the smallest of the four groups, was always successfully intubated.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 5000 patients undergoing screening colonoscopy, ~ 20% of patients stated that bowel preparation was one of the most worrisome factors before the planned procedure [ 18 ]. The authors of that study concluded that optimizing the taste of bowel preparations and the required volume intake would likely increase participation rates for screening colonoscopy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 5000 patients undergoing screening colonoscopy, ~ 20% of patients stated that bowel preparation was one of the most worrisome factors before the planned procedure [ 18 ]. The authors of that study concluded that optimizing the taste of bowel preparations and the required volume intake would likely increase participation rates for screening colonoscopy [ 18 ]. The current survey found that that most (84.7%) patients who reported previously taking a bowel preparation believed their experience with NER1006 was much better/better or about the same compared with that for the previously administered product.…”
Section: Discussionmentioning
confidence: 99%